Examining the Role of e-CRM in Boosting Customer Satisfaction in Financial Institutions in Nepal: A Two-Stage PLS-SEM and ANN Approach (Prithvi Academic Journal, 2025)
e-CRM has become a critical tool for enhancing customer satisfaction, particularly in financial institutions navigating the challenges of digital transformation. This study investigates the impact of key e-CRM components—Trust and Security, Personalization, Technology Infrastructure, Customer Data Management, Service Quality and Customer Engagement—on customer satisfaction. A causal-comparative research design was adopted, with data collected from 360 customers of financial institutions in Pokhara and analyzed using SEM-PLS and ANN methodologies. SEM-PLS results identified Trust and Security and Personalization as significant predictors, while ANN confirmed their high predictive importance, with Trust and Security achieving a normalized importance of 99.14 percent. The study concludes that building trust and delivering personalized services are paramount for enhancing customer satisfaction, while foundational e-CRM elements play a supportive role. Financial institutions should prioritize robust security and personalization strategies to optimize customer satisfaction and leverage advanced analytics like ANN for deeper insights. These findings provide a roadmap for financial institutions to develop customer-centric e-CRM strategies, contributing to both academic literature and practical applications.